Intervenciones de enfermería para la seguridad del paciente quirúrgico - Alvarado Chacón, Roberto Enrique; Cuello Freire, Guadalupe Eduvige; Guevara Guamán, Valeria Kasandra; Yamberla Fierro, Luis Alfredo (Revista Cubana de Investigaciones Biomédicas, 2024)
Patient safety is a global concern in healthcare, as it aims to minimize risks that compromise patient integrity in medical care settings. This concept encompasses a set of coordinated actions that promote safe practices and a culture of safety among healthcare professionals. This study aimed to describe nursing interventions focused on surgical patient safety through a literature review. A qualitative, documentary, non-experimental, and descriptive study was conducted, using the PRISMA 2020 flow diagram to select 10 relevant publications. The findings highlight that nursing professionals play a fundamental role in patient safety, marked by the rigor of their interventions and their continuous monitoring of patients until discharge. In most cases, nurses are the first to identify and report events that could jeopardize surgical patient safety. However, significant barriers were identified that hinder the implementation of these interventions, including personal, organizational, and process-related factors. Despite efforts, adherence to safety interventions remains insufficient, which contributes to issues such as medication administration errors and surgical site infections.